Case management effectiveness for managing chronic illnesses in Korea: a systematic review. (29th June 2018) - Joo, J.Y.; Liu, M.F.
Abstract : Background: Case management has been adopted in Korea and been recognized as a promising care‐coordination method that lowers costs and improves quality of care. However, the effectiveness of case management among individuals with chronic illnesses who reside in the community has yet to be established. Aim: This systematic review identifies and synthesizes recent evidence of case management's effectiveness in managing chronic illnesses among adults in Korea. Methods: The methodology of this systematic review was guided by the Cochrane processes and PRISMA statements. A search of multiple bibliographic databases to identify studies of case management in the populations of Koreans adult with chronic illnesses was conducted. Studies that met the inclusion criteria were published in English or Korean. Nine empirical peer‐reviewed studies published between 2008 and 2016 were selected for review. Results: The retrieved studies show that case management programmes in Korea for adults with chronic illness in the community were led by nurses. There was strong evidence that nurse‐led case management was effective in improving psychobehavioural and objective clinical outcomes; however, results for health services utilization outcomes were mixed. Conclusion: In future, research with rigorous study designs and large sample size in multiple settings are needed to further assess the effectiveness of case management in Korea. Implications for nursing and health policy: Nurse‐led case management would be of support in the care of chronic illnesses not only in Korea but also in Asian countries which share standard practice of case management with Korea. Nursing leaders should allocate resources to sponsor educational resources and practical strategies for evidence‐based case management.